Accurate measurements of Optical Turbulence with Sonic- anemometers. (March 2015) - Travouillon, T; Otarola, A; Els, S; Riddle, R; Schöck, M; Skidmore, W; Bibb, D
Abstract: The minimization of optical turbulence in and around the dome is key to reach optimum performance on large telescopes equipped with adaptive optics. We present the method and preliminary results of in-situ measurements of optical measurements made using sonic-anemometers. We show the impact of correcting the raw data for aliasing, path averaging, pulse sequence delays and Taylors' hypothesis. Finally, we highlight the occurrence of non-Kolmogorov turbulence which complicates the quantitative impact of the measurements on the telescope's resolution.